A pornografia como paródia: humor e crítica nos machinimas eróticos - Débora Krischke Leitão; Laura Graziela Gomes; Raira Bohrer dos Santos (Ciências Sociais Unisinos)
In this article, based on our ethnographic research conducted in a 3D virtual world, we discuss the production of erotic machinima as a form of altporn. Machinima is a technique that allows the production of films in digital platforms such as games and 3D virtual worlds. We argue that erotic machinimas, understood as parody of pornography itself, establish a critique of mainstream pornography.